Phenolic glycosides from the stems of Clerodendrum inerme Gaertn. collected in Vietnam - Minh, Tran Thi; Thuong, Nguyen Thi Minh; Thu, Nguyen Hoai; Nghia, Nhu Trong; Toan, Ho Khanh; Thanh, Nguyen Thi Viet; Huong, Tran Thu (Vietnam Journal of Science and Technology, 2021)
Five phenolic glycosides, clerodenoside A (1), seguinoside K (2), cistanoside D (3), verbascoside (4), and isoverbacoside (5) were isolated from the ethyl acetate soluble fraction of methanolic extract of the Clerodendrum inerme stems. Their structures were determined by spectroscopic analysis and comparison of spectral data with those reported in the literature. Compound 3 was isolated from this plant for the first time.